Heterologous expression of natural product biosynthetic gene clusters in Streptomyces coelicolor: from genome mining to manipulation of biosynthetic pathways. (1st February 2014) - Gomez-Escribano, Juan Pablo; Bibb, Mervyn J
Abstract: Heterologous gene expression is one of the main strategies used to access the full biosynthetic potential of actinomycetes, as well as to study the metabolic pathways of natural product biosynthesis and to create unnatural pathways. Streptomyces coelicolor A3(2) is the most studied member of the actinomycetes, bacteria renowned for their prolific capacity to synthesize a wide range of biologically active specialized metabolites. We review here the use of strains of this species for the heterologous production of structurally diverse actinomycete natural products.